Prolonged warming and drought modify belowground interactions for water among coexisting plants. (12th September 2018) - Grossiord, Charlotte; Sevanto, Sanna; Bonal, Damien; Borrego, Isaac; Dawson, Todd E; Ryan, Max; Wang, Wenzhi; McDowell, Nate G
Abstract: Understanding how climate alters plant–soil water dynamics, and its impact on physiological functions, is critical to improved predictions of vegetation responses to climate change. Here we analyzed how belowground interactions for water shift under warming and drought, and associated impacts on plant functions. In a semi-arid woodland, adult trees (piñon and juniper) and perennial grasses (blue grama) were exposed to warming and precipitation reduction. After 6 years of continuous treatment exposure, soil and plant water isotopic composition was measured to assess plant water uptake depths and community-level water source partitioning. Warming and drought modified plant water uptake depths. Under warming, contrasting changes in water sources between grasses and trees reduced belowground water source partitioning, resulting in higher interspecific competition for water. Under drought, shifts in trees and grass water sources to deeper soil layers resulted in the maintenance of the naturally occurring water source partitioning among species. Trees showed higher water stress, and reduced water use and photosynthesis in response to warming and drought. This case study demonstrates that neighboring plants shift their competitive interactions for water under prolonged warming and drought, but regardless of whether changes in moisture sources will result in increased competition among species or maintained partitioning of water resources, these competitive adaptations may easily be overridden by climate extremes.